Teaching question sentences by using Five Fingers Technique - Rahmi Daniati; Siti Sarah Fitriani; Diana Achmad (Universitas Syiah Kuala, 2017)
Grammar has an important role in building good sentences. In learning grammar, the students are usually taught about phrases, clauses, sentences, and also question sentences. Tocreate question sentences, there is a technique that can be used by the students; this is called five fingers technique. Therefore, this research aims to find out whether five fingers technique can improve the students’ ability in making question sentences. The study was encouraged by the problems faced by the students in learning question sentences and the need of fun activity in teaching learning process. This study used one group pre-test and post-test design. The sample of the study was class VIII-1 which consisted of 29 students. Random sampling technique was used by the writer to choose the sample. Based on the tests results, where the score of post-test was higher than the score of pre-test, it can be concluded that using five fingers technique which use the fingers as the tool to memorize the types of question sentences (wh-question, yes/no question, positive tag question, negative tag question, and assumption question) can improve the students’ ability in making question sentences. Therefore, it is recommended for the teachers to use five fingers technique in teaching question sentences.